Healthy by nature: natural treatment of disease - Schneider, Ernst (Madrid, Spain : Editorial Safeliz, 2008)
This volume deals with the treatment and prevention of more than two hundred diseases through natural means.
Includes index.
rua 23/06/14
Loans
Keywords: Alternative therapy; Healing & health; Healing agents